ABOUT THE CONTROLLED SINGLE-CHANNEL TRANSPORT DEVICES FUNCTIONAL SAFETY MODEL - Razghonov, S. A.; Lesnikova, I. Yu.; Oglih, V. V.; Shapovalov, O. V. (Systems and Technologies, 2025)
The article considers the functional safety of single-channel transport devices of robotic on-board systems. It is shown that the technical devices currently being developed are mostly covered by built-in control. The safety and reliability of single-channel controlled devices have not been given sufficient attention. Thus, in existing regulatory documents on reliability, a comprehensive reliability indicator (the device's readiness coefficient) is determined by the ratio of average work on refusal to the amount of average work on refusal and average recovery time. The values of the readiness coefficient are determined for the operating conditions of the object when the average failure of the refusal and the average duration of recovery remain constant. Such interpretation implies that any refusal of the device is detected and then immediately restored; that is, the built-in control tools are ideal. In real conditions, it is difficult to create controls that provide a complete guarantee of detection. The approach is considered that formalize applied functional safety problems and allows you to find optimal solutions to applied tasks. Technical devices the currently being developed are mostly covered by built-in control. The safety and reliability of single-channel controlled devices have not been given sufficient attention. The formula expressions of stationary probabilistic ones for renewed single-channel devices with built-in hardware have been obtained. They allow for taking into account the real characteristics of the efficiency and reliability of controls, while increasing the accuracy of the results of the analysis of the systems. It is known that the reliability of the transport device is the property to maintain performance for a given time with the preservation of the given performance characteristics under appropriate technical conditions of operation. This property is directly related to economic operational parameters. In the end, economic parameters, in modern conditions, play a crucial role in the production of this device and the business processes of operation. Briefly consider the time indicators of safety and reliability of a single-channel controlled device. The indicators of the duration of time between failures and separately between hidden failures, as well as the recovery time and downtime of the device, are determined.